Pelatihan Pembuatan Sabun Rosella di Gresik dalam Upaya Pencegahan Penularan COVID-19 Sebagai Implementasi SDGS-3: The Training in Preparation of Rosella Hand Soap in Gresik to Prevent Transmission of COVID-19 as Implementation of SDGS 3 - Juni Ekowati; Melanny Ika Sulistyowati; Achmad Toto Purnomo; Kholis Amalia Nofianti; Norhayati Norhayati; Gusti Rizaldi; Ghinalya Chalbi Ananda (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Efforts to inhibit the transmission of COVID-19 are continuing to this day. One of them is using hand-washing soap to prevent the transmission of this virus. The Faculty of Pharmacy, Airlangga University, seeks to implement SDGs-3 through community service activities to increase community empowerment, especially for the younger generation. The utilization of natural ingredients containing many active compounds has yet to be discovered. The solution is to provide information on the source of the active ingredients for hand washing soap, for example, the Rosella flower, explaining the mechanism of soap in inhibiting the spread of viruses and how to make hand washing soap. The activity was carried out in Gresik with counseling and training methods. The outcome was an increase in participants' understanding, as indicated by an average post-test score of >65, with an increase in score of >10% compared to the pretest. In addition, one product of Rosela flower hand washing soap was also obtained. From this activity, it was concluded that there was an increase in understanding of 28%. It is hoped that this increase in understanding and skills for the younger generation can mobilize the surrounding community so that prevention of the transmission of COVID-19 is more massive and conditions of good health and well-being in society will be achieved.